Development of load distribution concept for cross country skis - Schwencke, F. (Norwegian University of Science and Technology, 2019)
Having top performing skis is critical for a world class cross country skier to be able to fight for the medals in the Olympics, World Championships and other major races. Throughout the last decade, measuring ski properties has become increasingly important. Today, the Norwegian Olympic Foundation is in charge of measuring skis and technology development for the Norwegian national team. The Norwegian Olympic Foundation use pressure mats to measure pressure distribution, which is considered time consuming and costly if the accuracy of the measurements are to be satisfying. Pressure distribution is important for a skis performance as it has great influence on the friction between the snow and the base of the ski. The aim of this thesis is, therefore, to develop a concept that simplifies and more accurately measures pressure distribution over the length of the ski. The concept developed relies on a load sensor sliding under the length of the ski while the ski is loaded with a set point load in the area around the binding. The concept developed is based on the load sensor elevating the ski from the surface to get a proper reading. This results in a more concentrated load on the load sensor. With the use of pressure mats, on the other hand, the full contact area of the ski is naturally distributed on the pressure mats, which results in lower pressure compared to the concept developed. Another difference is that the developed concept is dependant on a spring in the loading mechanism to keep the applied load stable. For the pressure mats, a static load is used as no elevation of the ski is necessary. Test results shows continuous load curves with one peak on the front end and one peak on the back end of the ski. The pressure mats, on the other hand, show several peaks and lows on both ends of the ski. There are clear similarities between the developed concept and the pressure mats when it comes to the location of the peak pressure and how these peaks move with increasing applied load. The results from the thesis show that the concept has potential for further development as time usage and resolution can be improved compared to the pressure mats used by the Norwegian Olympic Foundation. Since the results cannot be directly compared to the results from the pressure mats, it is necessary to establish a base of measurements to ?nd potential relationships between snow conditions and skis. Further testing is crucial, but it is expected that the concept can contribute to improved understanding of the pressure distribution of a ski.